Correlation between nasopharyngoscopy and cephalometry in the diagnosis of hyperplasia of the pharyngeal tonsils - Ritzel, Rodrigo Agne; Berwig, Luana Cristina; da Silva, Ana Maria Toniolo; Corrêa, Eliane Castilhos Rodrigues; Serpa, Eliane Oliveira (International Archives of Otorhinolaryngology, 2012)
Introduction: Hyperplasia of the pharyngeal tonsil is one of the main causes of mouth breathing, and accurate diagnosis of this alteration is important for proper therapeutic planning. Therefore, studies have been conducted in order to provide information regarding the procedures that can be used for the diagnosis of pharyngeal obstruction.Objective: To verify the correlation between nasopharyngoscopy and cephalometric examinations in the diagnosis of pharyngeal tonsil hyperplasia.Method: This was a cross-sectional, clinical, experimental, and quantitative study. Fifty-five children took part in this study, 30 girls and 25 boys, aged between 7 and 11 years. The children underwent nasofibropharyngoscopic and cephalometric evaluation to determine the grade of nasopharyngeal obstruction. The Spearman's rank correlation coefficient at the 5% significance level was used to verify the correlation between these exams.Results: In the nasopharyngoscopy evaluation, most children showed grade 2 and 3 hyperplasia of the pharyngeal tonsil, which was followed by grade 1. In the cephalometry assessment, most children showed grade 1 hyperplasia of the pharyngeal tonsil, which was followed by grade 2. A statistically significant regular positive correlation was observed between the exams.Conclusion: It was concluded that the evaluation of the pharyngeal tonsil hyperplasia could be carried out by fiber optic nasopharyngoscopy and cephalometry, as these examinations were regularly correlated. However, it was found that cephalometry tended to underestimate the size of the pharyngeal tonsil relative to nasopharyngoscopy.
Keywords: mouth breathing; nasopharynx; diagnosis; comparative study